Application of the Throwing Catch Ball Method in Improving Learning Outcomes Volleyball Upper Passing at Junior Hight School Negeri 13 Palembang - Ariansyah, Febri; Usra, Meirizal (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This recearch employed a collaborative approach between the researcher and the teacher through the Classroom Action Research (CAR) method. The research was carried out over four face-to-face meetings, divided into two cycles, with each cycle consisting of two sessions. The purpose of this study was to determine the extent to which the implementation of the throw-and-catch ball method in volleyball learning could improve the overhead passing skills of students in Junior High School 13 Palembang. The subjects of this study were 10 students from Junior High School 13 Palembang. Data collection was conducted using observation sheets. The results of the study showed an improvement in overhead passing skills in volleyball through the application of the throw-and-catch ball method. Based on descriptive qualitative data analysis, the average student score in Cycle I was 22, which increased to 30 in Cycle II, indicating progress. The learning mastery level also improved from 63% in Cycle I to 85% in Cycle II, showing an increase of 22%.